Formulation of Natural Handsanitizer From Red Belt (Piper Crocatum) Leaves and Aloe Vera (Aloe Vera) - Hasni Yaturramadhan; Cory Linda Futri (Journal of Public Health and Pharmacy, 2021)
Itroduction: The government continues to strive so that the Corona virus no longer takes victims due to the Corona virus, of course as Indonesian people support the government's program well. Wash hands with soap so that the Corona Virus that sticks to our bodies is gone and always provide handsanitizer wherever we go. The purpose of this research is that people can make their own hand sanitizer at home. Methods: Materials for handsanitizer are 96% Alcohol, Red Betel Leaf (Piper Procatum), Aloe Vera (Aloe Vera) with preference test and allergy test. Result: The preference test and allergy test were carried out on 50 panelists, 45 people liked natural hand sanitizer Conclusion: Natural hand sanitizer is used to prevent the covid 19 virus